Clinical Evaluation, Diagnosis and Treatment of Pheochromocytoma - Romana Marušić; Tajana Turk; Tatjana Bačun (Acta Clinica Croatica)
Pheochromocytomas are rare neuroendocrine tumors that originate in chromaffin cells of the adrenal medulla and excessively secrete catecholamines, which leads to a multitude of different symptoms. The most common symptoms include headaches, palpitations, and sweating. Because of a diverse clinical presentation, pheochromocytomas pose a major diagnostic challenge and often go unidentified. These tumors can occur sporadically or as a part of hereditary syndromes. The diagnosis is confirmed by measuring plasma and 24-hour urinary metanephrine and normetanephrine. Computed tomography, magnetic resonance imaging, and functional morphological examinations are used for tumor localization. The treatment is operative and requires special preoperative patient preparation to prevent hypertensive crisis and arrhythmias. Due to the possibility of recurrence, the patient needs to be monitored. Pheochromocytoma has a high fatality rate if not recognized on time due to the effect of catecholamines on the cardiovascular system.